Effect of alpha thalassaemia trait and enhanced gamma chain production on disease severity in beta thalassaemia major and intermedia. Issue 1 (January 1994) - Gringras, P; Wonke, B; Old, J; Fitches, A; Valler, D; Kuan, A M; Hoffbrand, V
Abstract : One hundred and twenty patients with homozygous beta thalassaemia were selected to determine the clinical effects of certain genetic factors which may modify disease severity. Genetic analysis defined specific beta thalassaemia mutations, the alpha thalassaemia genotype, and the presence of an XmnI restriction enzyme site, associated with increased fetal haemoglobin (HbF) production under certain conditions. Genotypic data with globin chain synthesis were related to the age when regular transfusions began and subsequent pubertal development. This study showed that the major determinants of disease severity in beta thalassaemia were the beta thalassaemia mutations, with co-inheritance of alpha thalassaemia trait and coinheritance of a high HbF determinant acting as ameliorating factors. The presence of an alpha thalassaemia deletion significantly reduced initial disease severity, although the effect on pubertal development was less clear. It is concluded that detailed genetic analysis should be performed in all newly diagnosed patients with thalassaemia. This, in conjunction with clinical assessment, will help to predict disease severity and prognosis.